Kualitas Udara Ambien Karbon Monoksida (CO) di Terminal Paal Dua Kota Manado - Oksfriani Jufri Sumampouw; Trivena Mantow (Universitas Sam Ratulangi, 2024)
Background: Carbon monoxide (CO) is a gas produced from the combustion of imperfect fuels that is harmful because it can have serious health effects. Most of the CO gas is produced in the combustion of fossil fuels in the form of exhaust gases. Therefore, CO gas will be high on highways and terminals. The purpose of the study is to measure and find out what the air CO level is at the Paal Dua Terminal in Manado City. Methods: This is a laboratory-based descriptive observation research. The location of the research was carried out at 2 points, namely point 1 of the vehicle parking lot and point 2 of the vehicle entrance. The measurement of CO levels uses the CO Analyser tool with the NDIR method which refers to SNI 7119.10_2011 concerning carbon monoxide (CO) content tests. Measurements were carried out for 3 days for 1 hour at each point and 2 times each. Research Results: The results showed that the CO level of air at the Paal Dua Terminal still meets the quality standard requirements of PERMENKES RI No. 02 of 2023 concerning the Implementation Regulation of Regulation Number 66 of 2014 concerning Environmental Health, which is 10,000 μg/Nm3 with measurement results ranging from 469-4,489 μg/Nm3. Conclusion: It can be concluded that the CO level at the Paal Dua Terminal in Manado City still meets the requirements of the quality standards, so it is recommended that the Government should conduct emission tests from vehicle smoke at the Paal Dua Terminal in Manado City periodically.